Efeitos do aparelho de Herbst no tratamento proecoce da má oclusão classe II de Angle - Mendes, Ary José Dias; Sampaio, Luana Paz; Raveli, Taisa Boamorte; Landázuri, Denise Rocha Goes; Raveli, Dirceu Barnabé [UNESP] (My University, 2012)
Due to its high prevalence in general population, Angle Class II malocclusion has been widely studied by several authors, as well as the methods for its treatment. Among the possible treatment methods stands out the Herbst appliance. Reintroduced more than three decades ago in the orthodontics community, it became the most utilized appliance because it does not require patient compliance, and provides continued action through bilateral telescopic tubes. The objective of the present article was to demonstrate the early treatment of Class II Division 1 malocclusion with mandibular retrusion using Herbst appliance.

A Classe II de Angle tem sido amplamente pesquisada por diversos autores devido à grande incidência na população, juntamente os meios para o seu tratamento. Dentre os métodos de tratamento, destaca-se o aparelho de Herbst que foi reintroduzido a mais de 3 décadas na comunidade ortodôntica. Por ser um aparelho que independe da cooperação do paciente e por propiciar uma ação contínua através de tubos telescópicos bilaterais, tornou-se atualmente o aparelho mais utilizado. O objetivo deste trabalho é demonstrar o tratamento precoce da má oclusão de Classe II divisão 1ª com retrusão mandibular com o uso do aparelho de Herbst.
Effects of Herbst appliance in early treatment of angle class II malocclusion
Keywords: Class II malocclusion; Orthopedic appliance; Herbst appliance; Má oclusão classe II; Aparelhos ortopédicos; Aparelho de Herbst